Dry sliding wear behaviour of cold-sprayed Cu-MoS2 and Cu-MoS2-WC composite coatings: The influence of WC. (July 2018) - Zhang, Yinyin; Epshteyn, Yakov; Chromik, Richard R.
Abstract: Cold-sprayed Cu-MoS2 and Cu-MoS2 -WC composite coatings were studied for their sliding wear performance in dry nitrogen. Presence of WC particles reduced friction coefficient and improved wear resistance. Dynamics of material transfer, chemical and phase composition of third bodies in the contact were examined. WC particles helped to form transfer films and smooth wear tracks; while rough wear tracks with evidence of detachment were observed for the Cu-MoS2 . Subsurface microstructure of the Cu-MoS2 -WC wear tracks showed major microstructural change occurred around WC particles. Microstructure and thickness of the tribolayers at 100 and 1000 cycles exhibited minor changes. However, for Cu-MoS2, microstructural change took place more extensively with sliding, leading to unstable tribolayers, which contributed to crack formation, detachment, and eventually high wear. Highlights: Influence of WC on reciprocating sliding wear behaviour of cold-sprayed Cu-MoS2 and Cu-MoS2 -WC composites was examined. Presence of WC effectively reduced and homogenized friction coefficient and wear throughout the wear tracks. WC particles helped to form transfer films and smooth wear tracks during sliding. Subsurface microstructure showed major change occurred only around WC particles, leading to a more stable tribolayer.